"A Lot of Inner-city Kids": How Financial Aid Policies and Practices Reflect the Social Field of Color-Blind Racism at a Community College Urban Campus. Issue 1 (2nd January 2020) - White, Julie A.; Dache, Amalia
ABSTRACT: In the U.S. educational system of higher education, community colleges are positioned as the institutions of access, with student financial aid as the primary policy lever to drive student enrollment. However, completion rates at community colleges are the lowest of all institution types, and financial aid has not been adequate to provide full access to students most in need, who are disproportionately students of color. In light of this challenge, this study addresses the research question: How does the social field of color-blind racism function within financial aid processes and resources at a community college's suburban campus and urban campus? Utilizing case study methodology, data was gathered via brief interviews, participant observation, and in-depth interviews with students and financial aid staff. Findings reveal that resource allocation and student and staff perceptions reflected a social field of color-blind racist ideology. The under-resourcing and racist perceptions of the urban campus contribute to a perpetuation of White privilege, a devaluing of the urban campus students and staff, and continued barriers to the educational goals of students of color.